Safety Assessment of One Lactiplantibacillus plantarum Isolated from the Traditional Chinese Fermented Vegetables—Jiangshui - Dexin Ou; Na Ling; Xihao Wang; Yanyan Zou; Jingjing Dong; Danfeng Zhang; Yizhong Shen; Yingwang Ye (Foods, 2022)
Lactiplantibacillus plantarum is a kind of extensively utilized probiotic species, which plays a critical role in the prevention of pathogenic bacteria and development of functional probiotics. Our group previously isolated one Lactiplantibacillus from Jiang Shui, a traditional Chinese fermented vegetable, which remarkably inhibited the growth of Aspergillus flavus. Herein, the safety of this isolate was assessed to ensure its application feasibility in food industry. Firstly, the phenotypic analyses including tolerance to low pH and bile salt, aggregation ability, and hemolytic activity detection, indicated the isolate could survive and colonize in the gastrointestinal tract, without hemolysin activity. The susceptibilities of the isolate to eight antibiotics and the absence of most resistance genes were demonstrated by agar disk diffusion and PCR, respectively. Furthermore, no mortality or toxicity was observed in mice by in vivo tests using gross autopsy, hematology, serum biochemistry, and HE-staining. Taken together, this study demonstrated the safety of Lactiplantibacillus plantarum WYH as a probiotic strain in terms of phenotypic analyses, absence of antimicrobial resistance and toxin-related genes, as well as mice toxicity test, while supported the prospect of applying isolate in suppression of fungal growth and mycotoxin biosynthesis.